Newspaper Report about the Panevėžys Region in 1888, a Newspaper Report by Jan Michał Witort: the Egodocumentary and Documentary Value of Written Content - Bogdzevič, Monika; Vyšniauskas, Arūnas (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; abstract in English]In this publication the translation of the article written by Jan Witort (signed by initials J. W.) to the Lithuanian language is introduced. The original article in Polish, titled “Stosunki na Żmudzi”, was first published in the Polish newspaper “Kraj” distributed from Saint Petersburg in 1888. It is noted that the old text could be interesting to a nowadays’ reader as a valuable primary source, especially while researching different aspects of local history. Another question considered is whether the article could be defined as egodocumental heritage. The opinion is expressed, that it cannot be considered as egodocument, though it has inherent egodocumentary value. Some parts of the article reveal author’s-observer’s personality, feelings, evaluation, interests, hopes, aspirations and visions. With reference to J. Witort’s article and to some other publications the authors of this work have also examined the historical concepts of Panevėžys regional dependence and have admitted that in the course of time they had changed. Moreover, it is emphasized that the Polish and Lithuanian views on Samogitia (Žemaitija) and perceptions of the Lithuanian territory were not necessarily alike. Some of the differences between the treatments of territory are reflected nowadays both in Lithuanian and Polish scientific literature.